Combating greenwashers in emerging markets: A game-theoretical exploration of firms, customers and government regulations. (August 2020) - Huang, Hongfu; Xing, Xinjie; He, Yong; Gu, Xiaoyu
Highlights: Studying firms' pricing strategies in the presence of greenwashers in emerging markets. Establishing a two-period game model considering customers' greenness learning effect. Investigating impacts of greenness level and anti-greenwashing regulations. Showing that greenwashing might benefit both green and brown firms. Deriving government's optimal anti-greenwashing enforcement level. Abstract: The sustainability boom in developing countries has caused the emergence of greenwashing behaviors that are impeding sustainable progress in the third world. To combat greenwashing behaviors in emerging markets, this paper proposes a game-theory model that studies the competitive pricing strategies of green incumbents facing competition from greenwashing entrants in emerging markets. The research considers customer behaviors, greenwashing threats, and the different implications of anti-greenwashing government enforcement strategies. The results reveal that greenwashing acts are not always performed with negative intent, but benefit both green incumbents and total customer surplus if the market greenness gap is small. In addition, a loose enforcement level contributes to higher social welfare in emerging markets.